Assessment of TESDA's Kasambahay Training Program on selected homemaking activities - Trinidad, Emmanuel Joseph R. (College of Home Economics, University of the Philippines Diliman, 2015)
This study aims to assess the Technical Education and Skills Development Authority's (TESDA) kasambahay training program or also known as Household Services NCII on selected homemaking activities specifically; cleaning rooms, washing and ironing clothes, preparing meals and serving food. Kirkpatricks' Learning Evaluation Model was used to assess the training program based on the reaction, learning, and application of the kasambahays and the satisfaction of the kasambahays' employers. Through purposive sampling, data were collected from 30 kasambahays who were enrolled in this year's training program and 20 of their corresponding employers. Four facilitators of TESDA were also interviewed. A variety of data instruments were used, including kasambahays' pre-test and post test surveys, kasambahays' interviews, facilitators' interview, and employers' feedback survey. Results indicate that on the average, the perceived household skills levels of the kasambahays have improved a lot after undergoing the training. The kasambahays were able to satisfy tehir employers to a great extent as well in terms of the selected homemaking activities. The time used for assessing the application of kasambahays and satisfaction of the kasambahays' employers were limited only for two to three weeks of observation. Thus, a longer time to observe the kasambhays' improvement of their homemaking skills is recommended to be able to assess more comprehensively the effectiveness of the training program.